Efficacy of ultrasound guided pectoral nerves block in patients undergoing unilateral breast surgery : a randomized controlled trial - Ismail, Abdul Jabbar (2019)
Introduction: PECS II Block is an alternative technique to Morphine for patients undergoing unilateral breast surgeries as a part of multi-modal opioid-free postoperative analgesia. Objective: Assessment of efficacy and safety of PECS II Block against the routine use of strong opioid Morphine in patients undergoing unilateral breast surgeries. Methods: It was a randomized controlled clinical trial which had enrolled 60 patients diagnosed with breast cancer stage I and II undergoing unilateral breast surgery with axillary clearance. Participants were randomized into two treatment groups, one group receiving PECS II block with Ropivacaine 0.375% and another group receiving IV Morphine 0.1mg/kg prior to surgery. General Anaesthesia was administered throughout the surgery for both groups of patients. Results: Demographically, both groups were comparable in terms of age, height, weight, BMI, pre-operative blood pressure and heart rate (p > 0.05). The average time to perform PECS II Block was 17.7 (±7.72) minutes with no associated complications encountered. In the controlled group, there were statistically significant lower intraoperative systolic blood pressure (p = 0.03), and higher usage of intraoperative fentanyl (p < 0.01) and phenylephrine (p = 0.04), however, the absolute difference was not clinically significant. Although both groups show significant post-operative pain score reduction in the first 24 hours (p < 0.01), there were no statistically significant difference between the groups in terms of post-operative pain score (p = 0.51) and PCA morphine usage (p = 0.86). However, patients receiving PECS II block had up to 50% reduction in post-operative nausea and vomiting compared to the controlled group (p = 0.015). Conclusion: PECS II Block is a safe technique and as effective as intravenous morphine as an analgesic modality for unilateral breast surgery in addition to significantly reducing PONV risk.